Publication Trends on Higher-Order Thinking Skills and Science Process Skills in Elementary Schools (1992–2023): A Bibliometric Analysis of Science Education - Nugroho, Irham; Wilujeng, Insih; Pujaningsih; Sad Iman, Muis; Nadya Mahesawati, Putri (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
This study examines publication trends and thematic developments in research on Higher-Order Thinking Skills (HOTS) and Science Process Skills (SPS) in elementary science education. A bibliometric approach was employed to analyze Scopus-indexed publications from 1992 to 2023, using title, abstract, and keyword searches with queries such as ("Higher Order Thinking Skills" AND "Science Process Skills" AND "elementary science education"). The data were processed using the Bibliometrix package and BiblioShiny interface in RStudio to map growth patterns, identify influential sources, leading countries, and emerging research themes related to the integration of HOTS and SPS. The results show a significant increase in publications since 2014, with 322 documents identified. The Journal of Physics: Conference Series emerged as the leading source, while Indonesia and Malaysia were the top contributing countries. Thematic analysis revealed dominant clusters around inquiry learning, critical thinking, and digital assessment, with a noticeable shift towards applied instructional and assessment models that combine HOTS and SPS. This reflects the growing alignment of research with 21st-century education reforms emphasizing inquiry-based and problem-solving skills. The findings suggest a strong integration of HOTS and SPS in science education, but also highlight gaps in long-term classroom implementation, particularly in elementary school contexts. This study underscores the need for curriculum frameworks and teacher professional development programs focused on effectively integrating HOTS and SPS into elementary science education